2008
DOI: 10.1007/s10815-008-9230-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of estradiol on the expression of estrogen, progesterone, androgen, and prolactin receptors in human peritoneal fibroblasts

Abstract: The inflammatory-like changes manifested by adhesion fibroblasts enhance the anabolic hormones receptor expression (ER-alpha, ER-beta, PRL, and A-R), when exposed to estradiol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Assuming the same number of patients in the 2 groups, we needed 8 patients in each group. The choice of 30% difference was arbitrary, but based on 2 assumptions: in normal endometria, PR-B decreases during the secretory phase (10); in a previous study, peritoneal fibroblasts were treated with estradiol to mimic ovarian stimulation during ART, and we found a 10% increase in PR-A+B (8). …”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…Assuming the same number of patients in the 2 groups, we needed 8 patients in each group. The choice of 30% difference was arbitrary, but based on 2 assumptions: in normal endometria, PR-B decreases during the secretory phase (10); in a previous study, peritoneal fibroblasts were treated with estradiol to mimic ovarian stimulation during ART, and we found a 10% increase in PR-A+B (8). …”
Section: Methodsmentioning
confidence: 98%
“…To quantify each target transcript, a standard curve was constructed using a tenfold dilution series of β-actin standard plasmid (Invitrogen Corp, Carlsbaad, CA). We used β-actin as house-keeping gene in a previous study on peritoneal fibroblasts (8). However, other studies have reported on the stability of beta-actin in endometrial samples (9).…”
Section: Methodsmentioning
confidence: 99%
“…Jurkat cells (2 × 10 6 /mL) were then incubated in T25 flasks with 0, 4, or 40 pg/mL estradiol (E 2 ) for 48 hr. Based on recent studies, the 4 pg/mL estradiol level was used to correspond to the post‐menopausal levels (midpoint within the observed post‐menopausal range), 21 while 40 pg/mL estradiol represents a level associated with the mean of follicular and luteal phases of pre‐menopausal women 22 . For each set of estradiol conditions, cells were coincubated with 0.5 or 5 μ m of genistein, representing physiologically achievable levels with diets and/or supplements 23,24 .…”
Section: Methodsmentioning
confidence: 99%
“…To quantify each target transcript, a standard curve was constructed with the use of a tenfold dilution series of β -actin standard plasmid (Invitrogen). We used β -actin as housekeeping gene in previous studies on peritoneal fibroblasts (2, 27). Other studies have reported on the stability of β -actin in endometrial samples (28).…”
Section: Methodsmentioning
confidence: 99%